Factors that influence treatment delay in patients with colorectal cancer - Zarcos-Pedrinaci, Irene; Fernández López, Alberto; Téllez-Santana, Teresa; Rivas-Ruiz, Francisco; Rueda-Domínguez, Antonio; Morales-Suárez-Varela, María Manuela; Briones, Eduardo; Baré, Marisa; Escobar, Antonio; Sarasqueta, Cristina; Fernández-de Larrea-Baz, Nerea; Aguirre, Urko; et al. (IMPACT JOURNALS LLC, 2017)
A prospective study was performed of patients diagnosed with colorectal cancer (CRC), distinguishing between colonic and rectal location, to determine the factors that may provoke a delay in the first treatment (DFT) provided.2749 patients diagnosed with CRC were studied. The study population was recruited between June 2010 and December 2012. DFT is defined as time elapsed between diagnosis and first treatment exceeding 30 days.Excessive treatment delay was recorded in 65.5% of the cases, and was more prevalent among rectal cancer patients. Independent predictor variables of DFT in colon cancer patients were a low level of education, small tumour, ex-smoker, asymptomatic at diagnosis and following the application of screening. Among rectal cancer patients, the corresponding factors were primary school education and being asymptomatic.We conclude that treatment delay in CRC patients is affected not only by clinicopathological factors, but also by sociocultural ones. Greater attention should be paid by the healthcare provider to social groups with less formal education, in order to optimise treatment attention.
Keywords: Cancer; Colorectal; Delay; Education; Treatment